The impact of female university students' acceptance towards agriculture contract farming on Malaysian economy - Abu Samah, Bahaman; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril; Uli, Jegak (Academic Journals, 2011)
The emergence of agriculture contract farming as one of the recent agriculture branches has promised a lot of potential for income generating. However do the youths, as the pillar of this country accept this contract farming as one of their potential occupations? The focus of this study is to determine specifically the female youth acceptance towards agriculture contract farming. Based on simple random sampling, a total of 283 female university students studying in universities in Malaysia were selected as respondents for this study. SPSS software was used to run analyses such as Pearson product-moment correlation and Multiple Linear Regression. Based on the results, all the independent variables studied namely belief, knowledge, support and attitude have positive and significant relationship with acceptance towards agriculture contract farming. In addition, attitude was found as the main contributor for acceptance towards agriculture contract farming among female youth. One of the strategies to further enhance the acceptance towards agriculture contract farming among female youth is to establish contract farming club at the university level. It is also recommended that agriculture contract farming club can be initiated as one of the clubs placed under the Rakan Muda Program. Besides, persistent exposure to courses and seminars on agriculture contract farming should be provided to the interested female youth.